Hydrogen-resistant coating capable of being applied to inner surfaces of hydrogen conveying pipelines and IV-type hydrogen storage cylinders and preparation method of hydrogen-resistant coating

The hydrogen permeability problem was solved and significantly improved by coating polyethyleneimine-modified graphene oxide and ethylene-vinyl alcohol copolymer composite coating on the non-metallic plastic lining of the hydrogen transport pipeline and the type IV hydrogen storage bottle. Safety and life of the equipment.

CN119505607AActive Publication Date: 2025-02-25XIANGTAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411680961.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The non-metallic plastic linings of existing hydrogen transport pipelines and type IV hydrogen storage bottles are not sufficient to store and transport hydrogen for a long time, resulting in hydrogen permeability problems and affecting the safety and life of the equipment.

Method used

The polyethyleneimine-modified graphene oxide is combined with the ethylene-vinyl alcohol copolymer to form a hydrogen-resistance coating, which is constructed through the "similar and soluble" principle and the "brick wall structure" to reduce the hydrogen permeability.

Benefits of technology

This coating significantly reduces the permeability of hydrogen, which is reduced by more than 45% compared to the uncoated substrate material, improving the safety and life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005148324780000011
    Figure HDA0005148324780000011
Patent Text Reader

Abstract

The invention discloses a hydrogen-resistant coating capable of being applied to the inner surfaces of hydrogen delivery pipelines and IV-type hydrogen storage cylinders and a preparation method thereof, the coating takes ethylene-vinyl alcohol copolymer (EVOH) as a main raw material and polyethyleneimine (PEI) modified graphene oxide (GO) as a filler, a coating stock solution is prepared by adopting a solution compounding method, and the composition of the coating stock solution is (PEI-GO) X-EVOH (X = 0, 0.25%, 1%, 2% or 4%). The preparation method comprises the following steps: by taking nylon 6 as a matrix, cleaning and airing, firstly coating a layer of nylon treating agent to improve the adhesive force of the barrier coating and a substrate, airing at room temperature, and uniformly pouring a composite solution on the matrix. The preparation method of the coating is simple and convenient, the coating can be dried at 35 DEG C and then cured at room temperature, and too high temperature is not needed. The composite solution is good in dispersity and stability, and the composite coating is excellent in tensile property and hydrogen barrier property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inner surface treatment of hydrogen transmission pipelines and IV-type hydrogen storage cylinders, and in particular to a method for preparing a hydrogen barrier coating. Background Art

[0002] The development of renewable energy and non-polluting energy is an important topic in the current energy field, and hydrogen energy is an ideal medium for the large-scale development of renewable energy. Renewable energy can be converted into hydrogen energy and stored. For the large-scale use of hydrogen energy, "hydrogen transmission" is a crucial link.

[0003] At present, the main methods of transporting hydrogen in China are long-tube trailers and pipelines. Long-tube trailer hydrogen storage bottles are mainly divided into four types: I, II, III, and IV. The first three types have metal liners, and the lining materials are mostly metal steel, which means that the hydrogen storage bottle itself is relatively heavy and the hydrogen storage density is limited. At the same time, the accumulation and diffusion of hydrogen atoms in the metal liner lead to the "hydrogen embrittlement" phenomenon, which can easily cause material failure and safety problems. Type IV hydrogen storage bottles are different from the first three types of hydrogen storage bottles in that in order to further reduce the dead weight of high-pressure hydrogen storage containers, increase the system's hydrogen storage density, and avoid the "hydrogen embrittlement" problem, the metal lining is replaced with a plastic lining. The plastic lining of Type IV bottles is mostly made of high-density polyethylene (HDPE), polyamide (nylon PA6) or polyethylene terephthalate (PET) as the main materials. Pipeline transportation is divided into metal pipelines and non-metallic plastic composite pipelines. Similar to metal liner hydrogen storage bottles, metal pipelines also face the problem of shortened equipment life and safety caused by "hydrogen embrittlement". In the future, the market will increase the demand for lighter, more cost-effective and safer non-metallic hydrogen pipelines. However, whether it is a type IV hydrogen storage bottle or a non-metallic hydrogen pipeline, the non-metallic plastic lining alone is not enough to store and transport H2 for a long time. Applying a high barrier coating on the lining is an effective way to reduce hydrogen penetration. Summary of the invention

[0004] The purpose of the present invention is to provide a hydrogen barrier coating suitable for the inner surface of a hydrogen transmission pipeline and a type IV hydrogen storage bottle and a preparation method thereof, and to adopt surface treatment technology to reduce the hydrogen permeability of the material.

[0005] A hydrogen barrier coating that can be used for the inner surface of hydrogen transmission pipelines and type IV hydrogen storage tanks is formed on a nylon 6 substrate and is composed of graphene oxide (GO) modified by polyethyleneimine (PEI) and ethylene-vinyl alcohol copolymer (EVOH). The composition is (PEI-GO) X -EVOH (0%≤X≤4%), wherein X is the mass percentage of PEI-GO and EVOH.

[0006] Furthermore, the preparation method of the polyethyleneimine (PEI) modified graphene oxide (GO) is as follows:

[0007] Step G1, graphene oxide is ultrasonically dispersed in deionized water at a concentration of 1 mg / ml, and is ultrasonically dispersed for 1.5 h at room temperature;

[0008] Step G2, polyethyleneimine was dissolved in deionized water at a concentration of 10 mg / ml, stirred at room temperature for 1 h, and then slowly dripped into the constantly stirred graphene oxide solution, using a separatory funnel to control the dripping rate at 3 s / drop;

[0009] Step G3, using 0.25 mol / L NaOH solution to adjust the pH value of the mixed solution to 12, and then stirring the mixed solution at 80° C. for 12 h;

[0010] Step G4, washing the product of step G3 with deionized water for 3 times by centrifugation, filtering and vacuum freeze-drying the product for 12 hours;

[0011] Step G5, grinding the product and sieving it through a 200-mesh sieve to obtain the final product PEI-GO powder.

[0012] Furthermore, the composite solution (PEI-GO) X -EVOH (0% ≤ X ≤ 4%) is prepared as follows:

[0013] Step S1, dissolving EVOH solid particles in 90% glacial acetic acid at 80° C., wherein the mass fraction of EVOH is 3.33%;

[0014] Step S2, ultrasonically dispersing PEI-GO powder in 90% glacial acetic acid, wherein the PEI-GO concentration is 1 mg / ml;

[0015] Step S3, adding different masses of PEI-GO dispersion to the EVOH solution described in step S1, wherein the mass percentages of PEI-GO and EVOH are 0, 0.25%, 1%, 2%, and 4%, respectively, and stirring the mixed solution at 45°C for 2 hours, and then ultrasonicating at room temperature and 80W for 2 hours to obtain pure EVOH solution and (PEI-GO) 0.25% -EVOH, (PEI-GO) 1% -EVOH, (PEI-GO) 2% -EVOH, (PEI-GO) 4% -EVOH mixed solution.

[0016] Furthermore, the hydrogen barrier coating formed on the nylon 6 substrate is prepared as follows:

[0017] Step R1, ultrasonically clean the nylon 6 substrate with deionized water and ethanol three times respectively, and leave it at room temperature for 48 hours;

[0018] Step R2, placing the nylon 6 substrate in step R1 on a flat surface, evenly brushing a layer of nylon treatment agent thereon to form an adhesion layer on the nylon surface, and drying at room temperature for 30 minutes;

[0019] Step R3, take appropriate volume of EVOH, (PEI-GO) 0.25% -EVOH, (PEI-GO) 1% -EVOH, (PEI-GO) 2% -EVOH, (PEI-GO) 4% -EVOH solution was uniformly poured on the nylon substrate of step R2, vacuum dried at 35°C for 6 hours, and then cured at room temperature for 36 hours to form a barrier layer on the nylon surface.

[0020] Furthermore, the main components of the nylon treating agent described in step R2 are resin and curing agent, wherein the resin is one or more of epoxy resin, acrylic resin or bisphenol A resin.

[0021] Furthermore, the thickness of the adhesion layer in step R2 is 30-50 um.

[0022] Furthermore, the thickness of the barrier layer in step R3 is 150-200 um.

[0023] The present invention takes the polymer material ethylene-vinyl alcohol copolymer as the main body, and according to the principle of "like dissolves like", utilizes the poor solubility between the polar group "hydroxyl" in the ethylene-vinyl alcohol copolymer and the non-polar molecule "hydrogen" to achieve the hydrogen barrier effect at the dissolution level; at the same time, modified graphene oxide is introduced to construct a "brick wall structure" in the ethylene-vinyl alcohol copolymer to achieve the hydrogen barrier effect at the diffusion level. Compared with the prior art, the present invention has the following advantages and outstanding effects: the coating preparation method is simple, the coating can be dried at 35°C and then cured at room temperature without excessive temperature; the coating can control the coating thickness by controlling the casting amount of the composite solution; the coating has sufficient tensile strength, that is, it can withstand the tensile force that may be encountered in the application without breaking; the coating has excellent elongation at break, that is, the coating has good flexibility and can adapt to the thermal expansion and contraction of the substrate without cracking; the coating has a significant hydrogen barrier effect, and the hydrogen permeability of the hydrogen storage and transportation equipment substrate material coated with the coating is reduced by more than 45% under 23°C and 0.1MPa pressure conditions relative to the substrate material not coated with the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a diagram of (PEI-GO) in Example 1 0.25% -EVOH composite coating cross-sectional morphology under scanning electron microscope (SEM). DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0026] Example 1: (PEI-GO) 0.25% -EVOH composite coating

[0027] First, polyethyleneimine modified graphene oxide (PEI-GO) was prepared, and the specific steps were as follows:

[0028] Step G1, taking 300 mg of graphene oxide and ultrasonically dispersing it in 300 ml of deionized water at a concentration of 1 mg / ml, and ultrasonically dispersing it at room temperature for 1.5 hours to fully disperse it;

[0029] Step G2, polyethyleneimine was dissolved in deionized water to a concentration of 10 mg / ml, stirred at room temperature for 1 h, and then 30 ml of the polyethyleneimine solution was slowly dripped into the constantly stirred graphene oxide solution, using a separatory funnel to control the dripping rate at 3 s / drop;

[0030] Step G3, using 0.25 mol / L NaOH solution to adjust the pH value of the mixed solution to 12, and then stirring the mixed solution at 80° C. for 12 h;

[0031] Step G4, washing the product of step G3 with deionized water for 3 times by centrifugation, filtering and vacuum freeze-drying the product for 12 hours;

[0032] Step G5, grinding the product and sieving it through a 200-mesh sieve to obtain the final product PEI-GO powder.

[0033] Second preparation (PEI-GO) 0.25% -EVOH composite solution, the specific steps are as follows:

[0034] Step S1, dissolving EVOH solid particles in 90% glacial acetic acid at 80° C., wherein the mass fraction of EVOH is 3.33%;

[0035] Step S2, ultrasonically dispersing PEI-GO powder in 90% glacial acetic acid, wherein the PEI-GO concentration is 1 mg / ml;

[0036] Step S3, adding the PEI-GO dispersion to the EVOH solution described in step S1, wherein the mass percentage of PEI-GO and EVOH is 0.25%, the mixed solution is stirred at 45°C for 2h, and then ultrasonicated at room temperature and 80W for 2h to obtain (PEI-GO) 0.25% -EVOH mixed solution.

[0037] Finally, (PEI-GO) was coated on the nylon substrate. 0.25%-EVOH composite coating, the specific steps are as follows:

[0038] Step R1, ultrasonically clean the nylon 6 substrate with deionized water and ethanol three times respectively, and leave it at room temperature for 48 hours;

[0039] Step R2, placing the nylon 6 substrate in step R1 on a flat surface, evenly brushing a layer of nylon treatment agent thereon to form an adhesion layer on the nylon surface, and drying at room temperature for 30 minutes, the adhesion layer thickness is 30-50 um;

[0040] Step R3, take an appropriate volume of (PEI-GO) 0.25% -EVOH solution is uniformly poured on the nylon substrate of step R2, vacuum dried at 35°C for 6 hours, and then cured at room temperature for 36 hours to form a barrier layer on the nylon surface with a thickness of 150-200um.

[0041] Please refer to Figure 1, scanning electron microscopy of (PEI-GO) 0.25% -EVOH composite film cross-sectional morphology was characterized, and an obvious layered structure can be observed in the figure. This is because the modified graphene oxide forms a significant "brick wall structure" in EVOH, which increases the hydrogen diffusion path and slows down the diffusion rate.

[0042] Example 2: (PEI-GO) 1% -EVOH composite coating

[0043] The same as Example 1, except that the mass percentage of PEI-GO and EVOH in step S3 is 1%.

[0044] Example 3: Pure EVOH coating

[0045] Step 1: dissolving EVOH solid particles in 90% glacial acetic acid at 80° C., wherein the mass fraction of EVOH is 3.33%.

[0046] Step 2: ultrasonically clean the nylon 6 substrate with deionized water and ethanol three times respectively, and leave it at room temperature for 48 hours;

[0047] Step 3: Place the nylon 6 substrate described in step 2 on a flat surface, evenly apply a layer of nylon treatment agent thereon to form an adhesion layer on the nylon surface, and dry it at room temperature for 30 minutes. The thickness of the adhesion layer is 30-50 um.

[0048] Step 4: Take an appropriate volume of pure EVOH solution and pour it evenly on the nylon substrate described in step 3, vacuum dry it at 35°C for 6 hours, take it out and cure it at room temperature for 36 hours to form a barrier layer on the nylon surface. The thickness of the barrier layer is 150-200um.

[0049] It should be pointed out that the present invention includes but is not limited to the above-mentioned implementation cases, and all modifications and improvements made based on the concept of the present invention belong to the protection scope of the present invention.

Claims

1. A hydrogen barrier coating that can be used for the inner surface of a hydrogen transmission pipeline and a type IV hydrogen storage tank, characterized in that: Formed on a nylon 6 substrate, it is composed of graphene oxide (GO) modified by polyethyleneimine (PEI) and ethylene-vinyl alcohol copolymer (EVOH), and its composition is (PEI-GO) X -EVOH (0%≤X≤4%), wherein X is the mass percentage of PEI-GO and EVOH.

2. According to claim 1, a method for preparing a hydrogen barrier coating that can be used for the inner surface of a hydrogen transport pipeline and a type IV hydrogen storage tank, wherein the preparation method of the polyethyleneimine modified graphene oxide (PEI-GO) is as follows: Step G1, ultrasonically dispersing graphene oxide in deionized water at a concentration of 1 mg / ml, and ultrasonically dispersing for 1.5 h at room temperature to fully disperse it; Step G2, polyethyleneimine was dissolved in deionized water at a concentration of 10 mg / ml, stirred at room temperature for 1 h, and then slowly dripped into the constantly stirred graphene oxide solution, using a separatory funnel to control the dripping rate at 3 s / drop; Step G3, using 0.25 mol / L NaOH solution to adjust the pH value of the mixed solution to 12, and then stirring the mixed solution at 80° C. for 12 h; Step G4, washing the product of step G3 with deionized water for 3 times by centrifugation, filtering and vacuum freeze-drying the product for 12 hours; Step G5, grinding the product and sieving it through a 200-mesh sieve to obtain the final product PEI-GO powder.

3. According to claim 1, a method for preparing a hydrogen barrier coating that can be used for the inner surface of a hydrogen transport pipeline and a type IV hydrogen storage tank, wherein the composite solution (PEI-GO) X -EVOH (0% ≤ X ≤ 4%) is prepared as follows: Step S1, dissolving EVOH solid particles in 90% glacial acetic acid at 80° C., wherein the mass fraction of EVOH is 3.33%; Step S2, ultrasonically dispersing PEI-GO powder in 90% glacial acetic acid, wherein the PEI-GO concentration is 1 mg / ml; Step S3, adding different masses of PEI-GO dispersion to the EVOH solution described in step S1, wherein the mass percentages of PEI-GO and EVOH are 0, 0.25%, 1%, 2%, and 4%, respectively, and stirring the mixed solution at 45°C for 2 hours, and then ultrasonicating at room temperature and 80W for 2 hours to obtain pure EVOH solution and (PEI-GO) 0.25% -EVOH, (PEI-GO) 1% -EVOH, (PEI-GO) 2% -EVOH, (PEI-GO) 4% -EVOH mixed solution.

4. The method for preparing a hydrogen barrier coating that can be used for the inner surface of a hydrogen transmission pipeline and a type IV hydrogen storage tank according to claim 1, characterized in that: The mixed solution (PEI-GO) according to claim 3 X -EVOH (0%≤X≤4%) is used to prepare the hydrogen barrier coating described in claim 1, and the preparation method thereof is as follows: Step R1, ultrasonically clean the nylon 6 substrate with deionized water and ethanol three times respectively, and leave it at room temperature for 48 hours; Step R2, placing the nylon 6 substrate in step R1 on a flat surface, evenly brushing a layer of nylon treatment agent thereon to form an adhesion layer on the nylon surface, and drying at room temperature for 30 minutes; Step R3, take appropriate volume of EVOH, (PEI-GO) 0.25% -EVOH, (PEI-GO) 1% -EVOH, (PEI-GO) 2% -EVOH, (PEI-GO) 4% -EVOH solution was uniformly poured on the nylon substrate of step R2, vacuum dried at 35°C for 6 hours, and then cured at room temperature for 36 hours to form a barrier layer on the nylon surface.

5. The method for preparing a hydrogen barrier coating according to claim 4, wherein the main components of the nylon treatment agent are resin and curing agent, wherein the resin is one or more of epoxy resin, acrylic resin or bisphenol A resin.

6. The method for preparing the hydrogen barrier coating according to claim 4, wherein the thickness of the adhesion layer is 30-50 um.

7. The method for preparing the hydrogen barrier coating according to claim 4, wherein the thickness of the barrier layer is 150-200 um.

Citation Information

Patent Citations

  • Graphene / PEI (polyethyleneimine) gas barrier composite membrane and preparing method of graphene / PEI gas barrier composite membrane

    CN105038222A

  • Oriented composite film with high gas barrier property

    CN112280087A

  • Composite containing ethylene-modified polyvinyl alcohol

    JP2021006598A

  • Gas barrier transparent polymer composite films

    KR1020120024263A

  • Film-forming composition for metal surface, application method, polymer film, pipe comprising such a film and use of such a film against hydrogen embrittlement

    US20240425706A1